Novel reproductive mode in a torrent frog Micrixalus saxicola (Jerdon) from the Western Ghats, India - Gururaja, Kotambylu Vasudeva (Zootaxa, 2010)
Reproductive modes in anurans are highly diverse despite external fertilization being a constraint. There are 39 reproductive modes documented so far (Wells, 2007). An apparently new reproductive mode is reported in a torrent frog, Micrixalus saxicola, an endemic and ancient anuran frog of the Western Ghats, considering the type of cavity made inside the lotic water body, involvement of the female in digging the cavity and concealing the eggs.